2011
DOI: 10.1038/leu.2011.346
|View full text |Cite
|
Sign up to set email alerts
|

Management of treatment-emergent peripheral neuropathy in multiple myeloma

Abstract: Peripheral neuropathy (PN) is one of the most important complications of multiple myeloma (MM) treatment. PN can be caused by MM itself, either by the effects of the monoclonal protein or in the form of radiculopathy from direct compression, and particularly by certain therapies, including bortezomib, thalidomide, vinca alkaloids and cisplatin. Clinical evaluation has shown that up to 20% of MM patients have PN at diagnosis and as many as 75% may experience treatment-emergent PN during therapy. The incidence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
167
3
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(177 citation statements)
references
References 119 publications
3
167
3
4
Order By: Relevance
“…20 The incidence of peripheral neuropathy was 27% in the ixazomib group (15% had grade 1 events and 10%, grade 2 events) and 22% in the placebo group (14% had grade 1 events and 6%, grade 2 events); 2% of patients in each study group had grade 3 events, and no grade 4 or 5 events or serious adverse events of peripheral neuropathy were reported. The incidence of peripheral neuropathy with pain was 4% in the ixazomib group and 3% in the placebo group.…”
Section: Safetymentioning
confidence: 99%
“…20 The incidence of peripheral neuropathy was 27% in the ixazomib group (15% had grade 1 events and 10%, grade 2 events) and 22% in the placebo group (14% had grade 1 events and 6%, grade 2 events); 2% of patients in each study group had grade 3 events, and no grade 4 or 5 events or serious adverse events of peripheral neuropathy were reported. The incidence of peripheral neuropathy with pain was 4% in the ixazomib group and 3% in the placebo group.…”
Section: Safetymentioning
confidence: 99%
“…24,25 The introduction of subcutaneous administration has improved convenience compared with the intravenous approach and substantially reduced the risk of peripheral neuropathy (PN), 26 a major limiting factor for long-term administration. 27 Other studies have shown that once-weekly administration of bortezomib can significantly reduce the risk of PN while preserving efficacy. 28,29 Given this context, the development of an orally bioavailable PI with an improved toxicity profile would represent a major advance for MM therapy.…”
Section: Introductionmentioning
confidence: 99%
“…53 There are clear guidelines for the treatment of BiPNP (Table 3). 54 In case of BiPNP grade 1 with pain or grade 2, the bortezomib dose should be reduced to 1.0 mg/m 2 twice weekly or the treatment interval should be extended to 1.3 mg/m 2 once per week. In case of grade 2 with pain or grade 3 BiPNP treatment should be withheld until symptoms have resolved, then treatment can be re-initiated at a dose of 0.7 mg/m 2 once per week.…”
Section: Peripheral Neuropathymentioning
confidence: 99%
“…53 (Table 3). 10,13,54 Recommendations include patient monitoring at a monthly interval for the first 3 months of treatment to detect early signs of TiPNP and to continue regular monitoring during the entire treatment duration.…”
Section: Peripheral Neuropathymentioning
confidence: 99%
See 1 more Smart Citation